2010
DOI: 10.1158/0008-5472.can-10-1440
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Tumor-Targeted Vascular Disrupting Agent Activated by Membrane-Type Matrix Metalloproteinases

Abstract: Vascular disrupting agents (VDA) offer a strategy to starve solid tumors of nutrients and oxygen concomitant with tumor shrinkage. Several VDAs have progressed into early clinical trials, but their therapeutic value seems to be compromised by systemic toxicity. In this report, we describe the design and characterization of a novel VDA, ICT2588, that is nontoxic until activated specifically in the tumor by membrane-type 1 matrix metalloproteinase (MT1-MMP). HT1080 cancer cells expressing MT1-MMP were selectivel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 43 publications
7
75
0
Order By: Relevance
“…(19) We used 111 In-MT1-scFv and 111 In-MT1-diabody, in addition, 111 In-NC-scFv was used to evaluate nonspecific uptake into tumor cells. Although In-MT1-diabody showed significantly high accumulation in HT1080 indicating both had affinity for MT1-MMP in cells and retained their immunoreactivity for MT1-MMP after conjugation with p-SCN-Bn-DTPA and radiolabeling with 111 In.…”
Section: Discussionmentioning
confidence: 99%
“…(19) We used 111 In-MT1-scFv and 111 In-MT1-diabody, in addition, 111 In-NC-scFv was used to evaluate nonspecific uptake into tumor cells. Although In-MT1-diabody showed significantly high accumulation in HT1080 indicating both had affinity for MT1-MMP in cells and retained their immunoreactivity for MT1-MMP after conjugation with p-SCN-Bn-DTPA and radiolabeling with 111 In.…”
Section: Discussionmentioning
confidence: 99%
“…Activated by MT1-MMP, ICT-2588 has shown promise in preclinical studies, successfully achieving enhanced therapeutic index [72] , an absence of cardiotoxicity [73] , and activity in a range of tumor types, not least prostate cancer (activity in PC3 xenografts in mouse models) [73] . This potential for the treatment of prostate tumors led the authors to apply the same technology to paclitaxel, yielding ICT-3205 [74] .…”
Section: Opportunities For Drug Targetingmentioning
confidence: 99%
“…1 here ICT01-2588 (Figure 1), originally referred to as ICT2588 (Gill et al, 2008), is a novel tumor-targeted vascular disrupting agent activated by membrane-type matrix metalloproteinases (Atkinson et al, 2010;Ansar et al, 2014) which has demonstrated preclinical therapeutic activity against solid tumors and reduced potential for cardiovascular toxicity . In this paper we report results of TDA experiments on ICT01-2588 in the solvents dimethylsulfoxide (DMSO), methanol, and TDA alongside complementary DLS studies in a potential formulation medium Tris buffer containing 10% hydroxypropyl--cyclodextrin.…”
Section: Introductionmentioning
confidence: 99%